Countermarked coins from the west of the Euxine Pontus during the first half of the 3rd century BC - Marin , Steluța; Ioniță , Virgil (KOINON: The International Journal of Classical Numismatic Studies, 2024)
In the city of Istros, on the north-west coast of Pontus, the events of the 3rd century BC mark, as in other Greek cities, its historical and monetary development. The whole region was under the rule of Lysimachus, king of Thrace, and his death in 281 BC would lead to a power vacuum that would allow the Celts to move south in 279/278 BC. A powerful union of Celtic tribes moved from central Europe into the northern Balkan Peninsula. From there, some of them plundered Greek cities in their incursion southwards, damaging even the sanctuary of Delphi, where they were defeated and lost their leader Brennus. After the defeat, other tribes conquered Thrace and settled in an unspecified area of central Bulgaria, probably at Tulovo, near Kazanlãk, where they found the kingdom of Tylis. A group of Celts continued their journey south across the Strait of Bosphorus into Asia Minor, where they settled in the region that would bear their name, Gallatia, which comes from galati, as the Greeks called them. The establishment of the kingdom of Tylis would bring continued influence to bear on the old possessions of the Thracian king and put pressure on the Greek cities on the western shore of the Black Sea, which were forced to pay the Celts a heavy tribute.